Influence of socioeconomic conditions on access to oral health services: a scoping review (Research, Society and Development, 2022)
The aims of the study were to assess the availability of scientific evidence that correlates socioeconomic conditions with access to oral health services, to verify theories that explain this relationship and to identify gaps regarding them. The search for the articles was carried out in the Embase, Lilacs, PubMed / MEDLINE, Scielo, Web of Science and Open Gray databases and an analysis of the theory present in each of the selected articles was carried out. A total of 277 articles were identified, 9 of which were included in this review. Only two types of theories were used in these studies: the theory according to Andersen, which is focused on the influence of individual factors, mainly the self-perception of health on access to health services and the theory according to Penchansky & Thomas, which attributes the concept to relationship between service provision and individuals. We conclude that there is a tendency to expand the concept of access to health services, incorporating the use of these services.